Government Spending, Renewable Energy and Green Growth: Evidence from Vietnam - Le, Ngan My Thi; Luu, Ven Phuoc (International Journal of Energy Economics and Policy, 2026)
This study investigates the relationship between government spending, renewable energy development and carbon intensity in Vietnam, where carbon intensity is used as an indicator of green economic performance. Using annual time-series data for the period 2000–2021, an autoregressive distributed lag (ARDL) model is employed to capture both short and long-run dynamics among the variables. The empirical results confirm the existence of a long-run equilibrium relationship. Renewable energy development is found to reduce carbon intensity in both the short and long run, thereby improving environmental quality and supporting the transition towards a more sustainable, low-carbon economy. By contrast, aggregate government spending does not exert a clear direct effect on carbon intensity, suggesting that broad-based fiscal expansion alone may be insufficient to foster green growth without complementary, environmentally targeted policies. The findings highlight the importance for policymakers of accelerating renewable energy deployment, mainstreaming sustainability considerations into urban planning, and aligning public investment in technology and infrastructure with low-carbon development objectives to achieve durable reductions in emissions.